Acceptance of interactive multimedia learning software i-tutor Bahasa Melayu (i-tutor BM): Insights from rural secondary schools in Malaysia - Kenneth Robin; Sabariah Sharif; Nur Farha Shaafi; Tan Choon Keong (International Journal Of Modern Education (IJMOE), 2024)
The integration of technology in education has become increasingly vital, particularly in enhancing learning experiences in rural areas. Therefore, the aim of this study is to investigate the acceptance of an interactive multimedia learning software known as i-Tutor Bahasa Melayu (i-Tutor BM) among secondary school students in rural Malaysia. A questionnaire was adapted from Lewis (2019) to assess the software's usability (PU) and ease of use (PEU); distributed to 30 students who participated in the experimental study. The findings revealed high levels of both usability and ease of use, with average scores of 5.79 and 5.78 respectively. These results suggest that i-Tutor BM software is effective and user-friendly, indicating its potential to enhance learning outcomes in rural educational settings.